2001
DOI: 10.1074/jbc.m108113200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for the Cytoplasmic Tail Sequences of Emp24p and Erv25p in Transport between the Endoplasmic Reticulum and Golgi Complex

Abstract: Heteromeric complexes of p24 proteins cycle between early compartments of the secretory pathway and are required for efficient protein sorting. Here we investigated the role of cytoplasmically exposed tail sequences on two p24 proteins, Emp24p and Erv25p, in directing their movement and subcellular location in yeast. Studies on a series of deletion and chimeric Emp24p-Erv25p proteins indicated that the tail sequences impart distinct functional properties that were partially redundant but not entirely interchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 37 publications
4
83
0
Order By: Relevance
“…This is consistent with the fact that the addition of C-terminal tags had not impaired the function and localization of GMT. As similar cases, it has been reported that the C-terminal peptides of Erv25p (KNYFKTKHII) and Rer1p (KYRYIPLDIGKKKYSHSSN), which also recycle between the ER and Golgi, bind to coatomer (Belden and Barlowe, 2001;Sato et al, 2001). Rer1p localizes to the Golgi at the steady state (Sato et al, 2001), like GMT.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the fact that the addition of C-terminal tags had not impaired the function and localization of GMT. As similar cases, it has been reported that the C-terminal peptides of Erv25p (KNYFKTKHII) and Rer1p (KYRYIPLDIGKKKYSHSSN), which also recycle between the ER and Golgi, bind to coatomer (Belden and Barlowe, 2001;Sato et al, 2001). Rer1p localizes to the Golgi at the steady state (Sato et al, 2001), like GMT.…”
Section: Discussionmentioning
confidence: 98%
“…Appending the HA tag to the C terminus of full-length Erv26p also caused a shift in localization to Golgi membranes, although Erv26-HA displayed only mild reductions in pro-ALP transport and recognition by the COPII budding machinery. Based on these results, we conclude that the C-terminal tail of Erv26p contains COPI-and COPII-specific sorting signals that allow the protein to cycle between ER and Golgi compartments in accord with other shuttling cargo receptors (31,42,43). We suggest that removal of both transport signals in the tail deletion mutant (Erv26⌬C2-HA) produces a protein that is inefficiently packaged into COPII vesicles but ultimately traffics to the Golgi complex in a slower "bulk flow" manner.…”
Section: Discussionmentioning
confidence: 99%
“…As controls, cytoplasmic tail peptides of Erv25 were used. Under the conditions that reproduced the COPI binding to the Erv25 di-phenylalanine motif (YF in Erv25) (49), the Rrt6 tail peptide interacted with COPI in a manner dependent on the di-lysine motif (Fig. 7C).…”
Section: Rrt6 Has Structural Properties Characteristic Of Known P24mentioning
confidence: 99%
“…COPI/COPII Binding to p24 C-tail Peptides-In vitro COPI binding assay of p24 cytoplasmic tail peptides was done as in Belden and Barlowe (49). Synthetic peptides used were Erv25C (CLKNYFKTKHII), Erv25YF-AA (CLKNAAKTKHII), Rrt6C (CTYLIIKIKSNPSSHIKKKGL), and Rrt6-KQ (CTYLIIKIK-SNPSSHIQQQGL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation